Upaya Peningkatan Hasil Belajar Siswa Melalui Metode Belajar Tanya Jawab dan Penggunaan Media Belajar Power Point pada Mata Pelajaran Pembibitan Tanaman Perkebunan di Kelas XI ATP SMK Negeri 1 Ranah Pesisir - Marsisliswento Marsisliswento (Journal on Education, 2022)
This research is motivated by the low motivation of students to learn in the subject of Plantation Plant Seedlings in Class XI SMKN 1 Ranah Pesisir. This is shown by some students just sitting and silent when the lesson is in progress. Passive children do not want to ask questions when they encounter difficulties, they choose to be silent, only students with high abilities dare to express their opinions. So that it affects the classical mastery of the previous subject below 60%, while the classical mastery limit is above 75%. The purpose of this study was to determine the cause of the lack of student motivation in learning activities in the subject of Plantation Plant Seedlings in class XI ATP at SMK Negeri 1 Ranah Pesisir. The subjects in this study were students of class XI Competency in Agribusiness Plantation Plantation Skills at SMK Negeri 1 Ranah Pesisir, totaling 24 students. This research was carried out from July to September 2019 in the 2019/2020 Academic Year in Class XI of Plantation Agribusiness Skills Competence (ATP) at SMK Negeri 1 Ranah Pesisir. This research was conducted in two cycles. Where each cycle begins with planning, implementation, observation/reflection, and follow-up. The results showed student learning outcomes in the first cycle under the KKM A total of 8 students answered correctly and 4 students scored above the KKM, after the question and answer method and using power points increased learning outcomes in class XI ATP students where almost 11 students scored above the KKM and 4 students below the KKM. The increase in student learning activities has reached 52.78%, meaning that more than half of the students have responded to the questions asked by the teacher and are able to understand the learning material well.